2019
DOI: 10.5812/ijpbs.86645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interpersonal Psychotherapy Oriented Child Birth Education on Stress and Role Adaption in Mothers with Premature Birth: A Randomized Clinical Trial

Abstract: Background: Preterm labor is the most stressful experience for mothers. Consultation by interpersonal psychotherapy (IPT) approach is a method to support mothers with pre-term labor.Objectives: This study aimed to assess the effect of interpersonal psychotherapy oriented child birth education on adaptation role and stress in mothers of infants admitted to the intensive care unit.Methods: This randomized interventional study investigated 92 primiparous women with a newborn admitted to the newborn intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Seven RCT studies, 30 , 31 , 33 , 37 , 42 , 45 , 46 two quasi-experimental studies, 34 , 43 and one case-–control study 40 investigated different nursing strategies on the stress level of mothers of preterm infants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven RCT studies, 30 , 31 , 33 , 37 , 42 , 45 , 46 two quasi-experimental studies, 34 , 43 and one case-–control study 40 investigated different nursing strategies on the stress level of mothers of preterm infants.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies 30 , 31 , 33 , 34 , 37 , 42 , 43 , 45 consisting of six RCTs and two quasi-experimental studies reported mothers’ stress as the study outcome with the same scale. Interventions were including educational programme, spiritual care, telenursing, parent support programme, SSC, and guided family centred care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study by Pouyan et al (2019) suggested that the effect of interpersonal psychotherapy training on stress and adaptation to the maternal role for mothers with preterm delivery reduced maternal stress score and resulted in a better adaptation of mothers [ 30 ]. Similarly, the present study supported the positive effects of training for the mothers of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…The CRIBӀӀ, the revised version on CRIB, consists of five variables of birth weight based on gestational age, congenital abnormality, gender, body temperature on admission, and maximal base excess. Some researchers believe that the CRIBII has a higher value in predicting mortality rate of premature neonates with birth weight less than 1500 g (17) compared to birth weight and gestational age variables (18), and helps predict hospital mortality rate among premature infants (19).…”
Section: Introductionmentioning
confidence: 99%